Efficacy of Fosfomycin in Urinary Tract Infections Occurring During Pregnancy - Nazia Hakeem, Warsha Brij Lal, Sanam Imtiaz, Sadia Mushtaq, Saira Almas (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine efficacy of fosfomycin in urinary tract infections occurring during pregnancy. Study Design: Descriptive study. Study Settings: Obstetrics & Gynecology Ward Dow University OJHA Campus, Karachi. Duration of Study: 11-08-2021 till 12-02-2022 Subject and Methods: Total 147 pregnant women presented with urinary tract infections were enrolled. Detailed demographics were recorded after taking informed written consent. Participants were given fosfomycin sachet 3gm stat dose after confirmation of UTI symptoms and they were followed for about 13 days and advised to proceed for Urine C/S. Participants were assessed on the basis of persistent symptoms of UTI and identification of bacteria in urine C/S. Data was analyzed by SPSS 20.0. Results: The mean age of the patients was 29.41±4.71 years. Mean BMI recorded was 28.65±3.21 kg/m2. According to the efficacy of drug (fosfomycin ), UTI was cured in 89 (60.5%) patients. Conlcusion: The efficacy of fosfomycin in urinary tract infections occurring during pregnancy in our study was 60.5%. Keywords: Urinary Tract Infection (UTI), Efficacy, Fosfomycin